2022
DOI: 10.3389/fnhum.2022.783452
|View full text |Cite
|
Sign up to set email alerts
|

A Fully-Immersive Virtual Reality Setup to Study Gait Modulation

Abstract: Objective: Gait adaptation to environmental challenges is fundamental for independent and safe community ambulation. The possibility of precisely studying gait modulation using standardized protocols of gait analysis closely resembling everyday life scenarios is still an unmet need.Methods: We have developed a fully-immersive virtual reality (VR) environment where subjects have to adjust their walking pattern to avoid collision with a virtual agent (VA) crossing their gait trajectory. We collected kinematic da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
4

Relationship

4
4

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 64 publications
0
10
0
Order By: Relevance
“…This could justify the occurrence of freezing episodes when trunk action is needed to execute the motor program (e.g. during turning [49] or gait modulation [42]). During walking, excessive trunk rigidity would also prevent the attenuation of forces exchanged during locomotion and thus proper stabilization of the head, explaining the inability of fall-prone patients to cope with challenging walking conditions [16].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This could justify the occurrence of freezing episodes when trunk action is needed to execute the motor program (e.g. during turning [49] or gait modulation [42]). During walking, excessive trunk rigidity would also prevent the attenuation of forces exchanged during locomotion and thus proper stabilization of the head, explaining the inability of fall-prone patients to cope with challenging walking conditions [16].…”
Section: Discussionmentioning
confidence: 99%
“…For walking trials, left and right heel contacts were identified based on the heel vertical trajectories, and the left and right gait cycles were defined. Only gait cycles at steady-state velocity were selected for further analyses, as described in [42]. No patient experienced gait freezing during linear walking.…”
Section: Kinematic Analysismentioning
confidence: 99%
“…Similar reasoning can be applied to freezing of gait [76], where it is necessary to distinguish the actual episode of gait freezing from the component of standing while freezing, and attempting to overcome the freezing episode, as well as the physiological neural activity related to gait modulation [35]. This aspect has not yet been studied in a precise and standardized method [77].…”
Section: Discussionmentioning
confidence: 99%
“…Four markers were placed bilaterally on the two feet on the main anatomical landmarks (heels, outer ankle bones, fifth metatarsi and hallux tips) to allow the identification of gait cycle events (heel off and toe off) and the computation of gait spatiotemporal parameters. 46 During gait initiation, three additional markers were attached to the pelvis (on the anterior superior iliac spines and the middle point between the posterior superior iliac spines) to allow the estimation of the centre of mass (CoM). 46 During standing we computed the centre of pressure (CoP) trajectory length, medio-lateral and anterior-posterior range of oscillation, and the confidence ellipse 47 , as measures of balance control 47 .…”
Section: Kinematic Gait Analysismentioning
confidence: 99%